Case Report: Consecutive Adrenal Cushing’s Syndrome and Cushing’s Disease in a Patient With Somatic CTNNB1, USP8, and NR3C1 Mutations - Detomas, Mario; Altieri, Barbara; Schlötelburg, Wiebke; Appenzeller, Silke; Schlaffer, Sven; Coras, Roland; Schirbel, Andreas; Wild, Vanessa; Kroiss, Matthias; Sbiera, Silviu; Fassnacht, Martin; Deutschbein, Timo (Frontiers in Endocrinology, 2021)
The occurrence of different subtypes of endogenous Cushing’s syndrome (CS) in single individuals is extremely rare. We here present the case of a female patient who was successfully cured from adrenal CS 4 years before being diagnosed with Cushing’s disease (CD). The patient was diagnosed at the age of 50 with ACTH-independent CS and a left-sided adrenal adenoma, in January 2015. After adrenalectomy and histopathological confirmation of a cortisol-producing adrenocortical adenoma, biochemical hypercortisolism and clinical symptoms significantly improved. However, starting from 2018, the patient again developed signs and symptoms of recurrent CS. Subsequent biochemical and radiological workup suggested the presence of ACTH-dependent CS along with a pituitary microadenoma. The patient underwent successful transsphenoidal adenomectomy, and both postoperative adrenal insufficiency and histopathological workup confirmed the diagnosis of CD. Exome sequencing excluded a causative germline mutation but showed somatic mutations of the β-catenin protein gene (CTNNB1) in the adrenal adenoma, and of both the ubiquitin specific peptidase 8 (USP8) and the glucocorticoid receptor (NR3C1) genes in the pituitary adenoma. In conclusion, our case illustrates that both ACTH-independent and ACTH-dependent CS may develop in a single individual even without evidence for a common genetic background.